ARP2/3-dependent growth in the plant kingdom: SCARs for life - Yanagisawa, Makoto; Zhang, Chunhua; Szymanski, Daniel B. (Frontiers in Plant Science, 2013)
In the human experience SCARs are permanent reminders of past events, not always based on bad decisions, but always those in which an interplay of opposing forces leaves behind a clear record in the form of some permanent watery mark. During plant morphogenesis, SCARs are important proteins that reflect an unusual evolutionary outcome, in which the plant kingdom relies heavily on this single class of actin-related protein (ARP) 2/3 complex activator to dictate the time and place of actin filament nucleation. This unusually simple arrangement may serve as a permanent reminder that cell shape control in plants is fundamentally different from that of crawling cells in mammals that use the power of actin polymerization to define and maintain cell shape. In plant cells, actin filaments indirectly affect cell shape by determining the transport properties of organelles and cargo molecules that modulate the mechanical properties of the wall. It is becoming increasingly clear that polarized bundles of actin filaments operate at whole cell spatial scales to organize the cytoplasm and dictate the patterns of long-distance intracellular transport and secretion. The number of actin-binding proteins and actin filament nucleators that are known to participate in the process of actin network formation are rapidly increasing. In plants, formins and ARP2/3 are two important actin filament nucleators. This review will focus on ARP2/3, and the apparent reliance of most plant species on the SCAR/WAVE regulatory complex as the sole pathway for ARP2/3 activation.